SUPPORTIVE FACTORS INFLUENCING CUSTOMERS’ DECISION TO SWITCH FROM BNI MOBILE BANKING TO WONDR BY BNI: STUDY IN MANADO - Rundengan, Praycilia; Mangantar, Maryam; Rogi, Mirah (Universitas Sam Ratulangi, 2026)
his research aims to examine the factors influencing customers’ decisions to switch from BNI Mobile Banking to Wondr by BNI. The study focuses on three supportive factors derived from the Push–Pull Theory: dissatisfaction, alternative attractiveness, and promotion. Unlike most previous studies that apply the full Push–Pull–Mooring (PPM) framework, this research isolates only the push and pull factors to emphasize the main drivers that directly encourage switching behavior without considering inhibiting factors such as switching cost or inertia. The data were collected through an online questionnaire distributed via Google Forms to 110 respondents who were BNI customers and had experience using both BNI Mobile Banking and Wondr by BNI. The analysis was conducted using multiple linear regression with SPSS 29. The results reveal that while alternative attractiveness and promotion have a positive and significant effect on switching behavior, dissatisfaction does not significantly influence customers’ switching decisions. This indicates that users are not primarily driven by negative experiences with the old application, but rather by the attractiveness and promotional appeal of the new one. Keywords: Switching Behavior, Dissatisfaction, Alternative Attractiveness, Promotion, Mobile Banking